OUTCOME PASIEN POST OPERASI JANTUNG YANG MENDAPATKAN EDUKASI PRA OPERASI DI INTENSIVE CARDIAC CARE UNIT [OUTCOME OF POST-HEART SURGERY PATIENTS RECEIVING PRE-OPERATIVE EDUCATION IN THE INTENSIVE CARDIAC CARE UNIT] - Hasibuan, Elizabeth Friska; Adi, Vincentia Puspasari; Susanti, Sri Budi; Manik, Marisa Junianti; Sinulingga, Elysabeth (Universitas Pelita Harapan, 2024)
Cardiac surgery is an intervention to correct and improve the anatomy and function of the heart. The preparations made by the nurse include conducting an orientation involving introduction to the operating room and post-surgery, education to deal with anxiety and postoperative pain, deep breathing exercises and effective coughing, spirometry incentive exercises, and early mobilization so that the patient understands what will be experienced before and after the procedure in the intensive care unit. This study aimed to determine the outcome of post-cardiac surgery patients who received care education in a pre-operative orientation at the ICCU, a private hospital in western Indonesia. This research used a quantitative descriptive design and univariate statistical analysis with a sample size of 15 participants using an accidental sampling technique. The instruments used were pain measurement observation sheets with a numerical scale, spirometry to measure lung volume capacity, and mobilization observation checklists, as well as the Hospital Anxiety Depression Scale questionnaire to measure anxiety. All participants received preoperative education. The results showed that all participants experienced decreased pain levels and could mobilize early, gradually from 24 to 72 hours post-surgery. A total of 10(66.67%) participants had a mild level of anxiety 24 hours after heart surgery, and 11(73.34%) participants experienced a consistent increase in lung volume capacity. Pre-cardiac surgery education provides the expected post-operative outcomes: decreasing pain and anxiety levels, increasing lung volume capacity, and gradual mobilization. BAHASA INDONESIA Bedah jantung adalah suatu tindakan operasi untuk mengoreksi dan memperbaiki anatomi dan fungsi jantung. Persiapan yang dilakukan perawat adalah melakukan orientasi meliputi pengenalan ruangan tindakan dan post operasi, edukasi untuk mengatasi kecemasan dan nyeri post operasi, latihan nafas dalam dan batuk efektif, latihan insentive spirometri serta mobilisasi dini, sehingga pasien memahami apa yang akan dialami sebelum dan sesudah tindakan operasi di ruangan intensif. Penelitian ini bertujuan untuk mengetahui gambaran outcome pasien post operasi jantung yang menerima edukasi perawatan dalam orientasi pre operasi di ICCU salah satu rumah sakit swasta di Indonesia bagian barat. Penelitian ini menggunakan desain deskriptif kuantitatif dan analisis statistik univariat dengan jumlah sampel 15 partisipan menggunakan tehnik accidental sampling. Instrumen yang digunakan berupa lembar observasi pengukuran nyeri dengan skala numerik, spirometri untuk mengukur kapasitas volume paru, dan ceklis observasi mobilisasi, serta kuesioner Hospital Anxiety Depression Scale untuk mengukur kecemasan. Seluruh partisipan mendapatkan edukasi pre operasi. Hasil menunjukkan seluruh partisipan mengalami penurunan tingkat nyeri dan mampu mobilisasi dini bertahap dari 24 jam sampai 72 jam post operasi. Sebanyak 10(66,67%) partisipan memiliki kecemasan tingkat ringan pada 24 jam post bedah jantung, dan 11(73,34%) partisipan mengalami kenaikan kapasitas volume paru secara konsisten. Edukasi pre operasi jantung memberikan outcome post operasi yang diharapkan yakni penurunan tingkat nyeri dan kecemasan, kenaikan kapasitas volume paru dan mobilisasi secara bertahap.